Sustainable Places 2019 2019
DOI: 10.3390/proceedings2019020025
|View full text |Cite
|
Sign up to set email alerts
|

Community-Based Virtual Power Plants: Against All Odds?

Abstract: Based on a European project entitled “Community-based Virtual Power Plants’ (Interreg 2017–2010) this paper discusses opportunities for community energy projects—focusing on the example of community-based virtual power plants. Using a business model canvas as heuristic and the Dutch demonstration case as an example, we show how a business model following a community logic is unfeasible in practice. The current institutional context compels community based cVPP initiatives to partially abandon such community-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The simulation results demonstrated that this model is beneficial in maximizing profit and minimizing emissions, which has a favorable influence on the environment. The authors of [14] presented a community-based VPP business model. It was found that the institutional and regulatory frameworks in place today provide significant challenges for the business model.…”
Section: IImentioning
confidence: 99%
“…The simulation results demonstrated that this model is beneficial in maximizing profit and minimizing emissions, which has a favorable influence on the environment. The authors of [14] presented a community-based VPP business model. It was found that the institutional and regulatory frameworks in place today provide significant challenges for the business model.…”
Section: IImentioning
confidence: 99%